The Challenge of Geography for Primary Children - Catling, Simon (Journal of Geography Education, 2022)
This article examines several challenges of including Geography in the primary grades curriculum. Challenge requires that younger children must become informed, consider, critique, reflect on and much more in studying Geography, not least to excite their interest and engagement, from their earliest school years. It involves developing their knowledge and understanding of the world today. This article explores aspects of children’s Geographies, that understanding Geography is essential for children, the significance of progression, the subject’s nature and purpose for primary children, and the importance of its high quality teaching. It concludes by articulating ten challenges for primary Geography.